2020
DOI: 10.1080/07317115.2020.1740904
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Cognitive Model for Behavioral Interventions in Older Adults with Behavioral and Psychological Symptoms of Dementia

Abstract: Objectives: The purpose of this study was to develop an individually tailored, nonpharmacological treatment model, the Cognitive Model for Behavioral Interventions (CoMBI), for patients with Behavioral and Psychological Symptoms of Dementia (BPSD) and comorbid maladaptive personality traits (CMPT), and to explore its feasibility and effectiveness. Methods: CoMBI was developed and implemented in two geriatric psychiatric inpatient wards in the Netherlands. In this single-group pretest-posttest, feasibility stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The evidence suggests that premorbid cluster A and C personality traits are associated with agitation, psychosis and depression in patients with dementia. A cognitivebehavioural framework called the 'ABC-model' was studied in Dutch nursing homes by Ekiz et al (2020) (2) intervention attitude, and (3) interventions aimed at the environment. CoMBI was associated with a reduction in frequency and severity of BPSD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence suggests that premorbid cluster A and C personality traits are associated with agitation, psychosis and depression in patients with dementia. A cognitivebehavioural framework called the 'ABC-model' was studied in Dutch nursing homes by Ekiz et al (2020) (2) intervention attitude, and (3) interventions aimed at the environment. CoMBI was associated with a reduction in frequency and severity of BPSD.…”
mentioning
confidence: 99%
“…The evidence suggests that premorbid cluster A and C personality traits are associated with agitation, psychosis and depression in patients with dementia. A cognitive‐behavioural framework called the ‘ABC‐model’ was studied in Dutch nursing homes by Ekiz et al (2020) as a feasible treatment of behavioural and psychological symptoms of dementia (BPSD). In this model, every Action starts Because of something in the environment and is continued by Consequences.…”
mentioning
confidence: 99%
“…Bosse et al [20] presented a visual attention cognitive model used to develop a software agent that assists a naval warfare officer in compiling a tactical picture of the situation on the field. Ekiz et al [21] proposed a cognitive model which is helpful to treat patients with Behavioral and Psychological Symptoms of Dementia. Basu et al [22] proposed a cognitive model of the bio-inspired approach used to find the optimal task Int J Artif Intell ISSN: 2252-8938  scheduling solution for internet of things (IoT) applications in a heterogeneous multiprocessor cloud environment.…”
Section: Related Workmentioning
confidence: 99%
“…Two single-group pre-post studies with a moderate risk of bias [39][40][41] and one with high risk of bias 42 reported global improvements in neuropsychiatric symptom severity on the Neuropsychiatric Inventory among people with dementia from admission to discharge in a specialised older persons' mental health inpatient ward. Results of one of these, however, represent only approximately 13% of admissions and those with a longer stay overall.…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%
“…Results of one of these, however, represent only approximately 13% of admissions and those with a longer stay overall. 42 Cheung et al 43 reported improvement in both global psychosocial functioning and the neuropsychiatric subscales of the Health of the Nation Outcome Scales (HoNOS) from admission to discharge from a specialised older persons' mental health inpatient ward among both people with dementia and older people with a mental disorder (Level IV).…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%